Ganho de contraste do potencial cortical provocado visual multifocal: efeitos da excentricidade e do modo de estimulação - SILVA, Veronica Gabriela Ribeiro da (Universidade Federal do Pará, 2017)
This study evaluated effects of eccentricity and mode presentation on the multifocal visual evoked potential (mfVEPS) recordings extracted by second-order kernels and its possible contributions from parallel visual pathways. Nine subjects (22.5 ± 3.7 years-old) were studied. All the subjects had 20/20 or corrected visual acuity and no previous history of neuro-ophtahlmic diseases or degenerative diseases. The subjects were tested with non dilated pupil in a monocular way. All the experimental procedures agreed to the tenets of Helsinki and were approved by Committee for Ethic in Research of Nucleus of Tropical Medicine (023/2011 protocol, Federal University of Pará, Belém, PA, Brazil). A CRT monitor displayed a 22º radius, 60 sectors dartboard, each sector with 16 checks (8 white and 8 black), pattern mean luminance of 40 cd/m2. The pattern selection to be shown in each sector was temporally modulated according to a binary pseudorandom m-sequence. Two stimulation protocols were used and we called them as pattern reversal and pattern pulse. Stimulus was presented at five Michelson contrast levels (100%, 50%, 25%, 12.5%, and 6.25%) in two trials with increasing and decreasing contrast order. The subject was instructed to keep the eye in a red cross (1º) placed at the center of the screen. Veris 6.01 was used to configure the stimuli. mfVEPs were recorded with gold cup electrodes: the reference electrode was placed at the inion; the recording electrodes were placed at, 4 cm above the inion (channel 1), 1 cm above and 4 cm to the right of the inion (channel 2), 1 cm above and 4 cm to the left of the inion (channel 3). Ground surface electrode was placed at the forehead. Skin impedance was kept below 5 KOhm. Recordings were amplified 100.000x, band-pass filtered between 3 and 100 Hz. The Veris 6.1 performed an offline low-pass filtering at 35 Hz. Veris 6.1 was used to extract first (K2.1) and second (K2.2) slices from second-order kernels data from original channels. Using MATLAB routines three additional channels were computed from the subtraction of the three original channels. For each subject, a signal-to-noise ratio (SNR) evaluation was performed over the averaged data of two trials in each one of the 6 channels. We measured the RMS amplitude of signal and noise interval of each recording. Finally, we analyzed the waveforms with best SNR for each sector. Mean RMS amplitude for each of six eccentric rings (R1 and R6 are the inner and outer rings, respectively) and for all rings together as a function of stimulus contrast was modeled using Michaelis-Menten functions. Semi-saturation constant (C50) of the contrast-response function was used as indicator of response contrast gain. For pattern reversal protocol contrast-response functions from K2.1/K2.2 had the following C50 values: R1: 35,5% ± 9,3; R2: 26,5% ± 6,5; R3: 22,4% ± 8,8; R4: 18,4% ± 4,4; R5: 20,6% ± 9,3; R6: 26,7% ± 12 / R1: 38,4% ± 4,2; R2: 27,4% ± 7,4; R3: 20,2% ± 4,9; R4: 22,4% ± 4,2; R5: 18,7% ± 3,2; R6: 23,1% ± 8,9. For pattern pulse protocol contrast-response functions from K2.1/K2.2 had the following C50 values: R1: 0; R2: 44,7% ± 10,5; R3: 38,3% ± 12,1; R4: 45,8% ± 12,1; R5: 49,4% ± 16,1; R6: 47,8% ± 14,7 / R1: 0; R2: 50,2% ± 10,3; R3: 48,2% ± 11,1; R4: 28,5% ± 4,2; R5: 54,3% ± 16,2; R6: 0. Two contrast sensitivity mechanisms contribute to mfVEPs elicited by stimuli located in the central visual field, one mechanism with higher contrast gain (pattern reversal mfVEP) and other mechanism with low contrast gain (pattern pulse). For stimulus at the periphery visual field, mechanism with high contrast gain contributed to the generation of mfVEPs elicited by all stimulation modes.